Bursicon mediates antimicrobial peptide gene expression to enhance crowded larval prophylactic immunity in the oriental armyworm, Mythimna separata - Kong, Hailong; Jing, Wanghui; Yuan, Lin; Dong, Chuanlei; Zheng, Minyuan; Tian, Zhen; Hou, Qiuli; Cheng, Yunxia; Zhang, Lei; Jiang, Xingfu; Luo, Lizhi (Developmental and comparative immunology, 2021)
It has been reported that a high population density alters insect prophylactic immunity. Bursicon plays a key role in the prophylactic immunity of newly emerged adults. In this paper, full-length cDNAs encoding the alpha and beta subunits of bursicon in Mythimna separata larvae (Msburs α and Msburs β) were identified. The cDNAs of Msburs α and Msburs β contain open reading frames (ORFs) encoding 145- and 139-amino acid residue proteins, respectively. Multiple alignment sequences and phylogenetic analysis indicated that Msbursicons (Msburs α and Msburs β) are orthologous to bursicons in other lepidopterans. The Msbursicons were expressed throughout all developmental states with higher relative expression during the egg, pupae, and adult stages. Msbursicons (Msburs α and Msburs β) were highly expressed in the ventral nerve cord and brain relative to other tested tissues. Msbursicon expression of larvae subject to high-density treatment (10 larvae per jar) was significantly increased compared with that of the larvae subject to low-density treatment (1 larva per jar) in the whole fourth and fifth instar stages. The trend in the expression of the antimicrobial peptide (AMP) genes cecropin C and defensin in the test stage was accorded and delayed with increased expression of bursicons. Silencing Msburs α (or Msburs β) expression by dsRNA injection in larvae subject to high-density treatment significantly decreased the expression levels of the cecropin C and defensin genes. Recombinant Msbursicon homodimers significantly induced the expression of the cecropin C and defensin genes. There was a notable decrease in the survival rate of the Msburs α (or Msburs β or Mscecropin C or Msdefensin) knockdown larvae infected by Beauveria thuringiensis. Our findings provide the first insights into how larval density mediates AMP gene expression, which subsequently affects the prophylactic immunity of insects under high-density conditions. •Bursicon genes (bursα and bursβ) from Oriental armyworm, M. separata was first isolated and identified.•High density significantly enhanced in bursicon genes expression in the larvae of M. separata.•The changed trend in AMPs expression of larvae from different density treatments was accorded and delayed with increased expression of bursicons.•Significant down-regulated (or up-regulated) expression of AMPs in the Msbursicon gene knockdown (or injection their homodimers) larvae.•There was notable decrease in the survival against Beauveria thuringiensis infection of the bursion (or AMPs) gene knockdown high density larvae.